Harmony of Bank Structure Ownership through Tri Hita Karana Cultural Concept - Sukendri, Nengah; Muktiyanto, Ali; Geraldina , Ira; Safitri, Julia (JASF: Journal of Accounting and Strategic Finance, 2023)
Tri Hita Karana is a philosophy of balance originating from Bali. From a banking perspective, Parahyangan can be interpreted as ethical and responsible governance. Pawongan reflects the balance of interests between various interested parties, from shareholders to management, employees, and customers. Palemahan is the bank's commitment to supporting sustainable and environmentally friendly economic development. This study aims to explore the harmonization of bank ownership through the cultural principles of Tri Hita Karana. The method in this article is a descriptive qualitative approach with a literature review that explores local wisdom theory specifically. Implementing Tri Hita Karana principles can create a more harmonious, transparent, and sustainable bank ownership structure. This can be achieved through strong governance policies, balanced ownership distribution, and commitment to social and environmental responsibility. Harmonizing the bank ownership structure through Tri Hita Karana can improve bank performance, strengthen public trust, and comprehensively contribute to the financial system's stability. Through the Tri Hita Karana Concept, the Bank Ownership Structure is a financial matter and a vehicle to realize harmonization between religious values and spirituality, common welfare, and environmental sustainability. The harmony model of the Tri Hita Karana-based bank ownership structure illustrates that by integrating Tri Hita Karana, Corporate Social Responsibility, and Triple Bottom Line, organizations can balance spiritual, social, environmental, and economic aspects and ensure long-term sustainability.